Maternal periodontal disease as a factor associated with low birth weight - Cruz, Simone Seixas da; Costa, Maria da Conceição N; Gomes Filho, Isaac Suzart; Vianna, Maria Isabel P; Santos, Carlos Teles (Revista de Saúde Pública, 2005)
OBJECTIVE: Recent studies have presented evidence that periodontal disease in pregnant women may be a determining factor for low birth weight. The present investigation was carried out to verify whether or not there is an association between maternal periodontal disease and low birth weight. METHODS: This was a case-control study on 302 women, of whom 102 were the mothers of live newborns of low weight (case group) and 200 were the mothers of live newborns of normal birth weight (control group). The existence of an association between periodontal disease and low birth weight was evaluated by means of a multivariate logistic regression model that considered other risk factors for low weight. RESULTS: The two groups were comparable with regard to age, height, pre-gestational weight, smoking, alcohol use, previous diseases, marital status, socioeconomic status, frequency of tooth-brushing and use of dental floss, number of meals per day and visits to the dentist. Periodontal disease was diagnosed in 57.8% of the mothers in the case group and 39.0% in the control group. Logistic regression analysis indicated a positive association between periodontal disease and low birth weight (unadjusted OR=2.15; 95% CI: 1.32-3.48), especially among the mothers with schooling of less than or equal to four years (ORadjusted=3.98; 95% CI: 1.58-10.10). CONCLUSIONS: Periodontal disease is a possible risk factor for low birth weight.